Temporal Trends and Spatial Patterns of Forest Fires in Central Kalimantan: Implications for Fire Management Policies - Saputra, Aswin Nur; Rixal, Rixal; Pamuji, Rizky; Al Arief, Yusuf (JURNAL GEOGRAFI, 2025)
Forest and land fires remain a significant environmental challenge in Central Kalimantan, Indonesia, causing extensive ecological, economic, and health impacts. This research investigates the spatial distribution and concentration of forest and land fire hotspots in the region from 2018 to 2024. Hotspot data from the SIPONGI system were processed using kernel density estimation to generate density maps, which were subsequently overlaid to pinpoint areas with the highest fire concentrations. The analysis identified 2019 as the year with the most severe fire occurrences, with Pulang Pisau District emerging as the region with the greatest fire intensity. These findings offer critical insights for directing fire prevention efforts and enhancing land management strategies to mitigate future fire risks in Central Kalimantan.